PENGARUH MOTIVASI, GENDER, SELF EFFICACY, DAN PERTIMBANGAN PASAR KERJA TERHADAP MINAT BERKARIER MENJADI AKUNTAN PUBLIK, KONSULTAN PAJAK DAN BANKIR - Fashihanin Kaulika Ulma; Khanifah Khanifah; Sri Retnoningsih (Universitas Katolik Indonesia Atma Jaya, 2023)
This study aims to determine whether Motivation, Gender, Self-Efficacy, and Labor Market Considerations partially and simultaneously affect the career interests of accounting students at Wahid Hasyim University Semarang as public accountants, tax consultants and bankers. This study uses quantitative data with a sample of 100 students as respondents. Sampling using purposive sampling technique. The type of data used is primary data. Data analysis using Statistical Package Social Science (SPSS) version 16. The results of this study parcial that Motivation has a positive and significant effect on career interest as a public accountant, tax consultant and banker. In addition, Gender has a positive and significant effect on interest in a career as a public accountant, tax consultant and banker. Self-efficacy has a positive and significant effect on. career. interest as a public accountant, tax consultant and banker. .Labor Market considerations have a positive and significant impact on career interest in becoming a public accountant, consultant and banker. The results .of the research simultaneously and together also show that Motivation, Gender, Self-eEficacy and Labor Market .Considerations have a positive and significant effect on .career interest as a public accountant, tax consultant and banker.